Enhancement Of Aodv Routing Protocol In Masnets - Jambli, M.N.; Wan Mohd Shuhaimi, W.B.; Lenando, H.; Abdullah, J.; Mohamad Suhaili, S. (2015)
The rapid development of wireless communication technologies and portable mobile devices such as laptops, PDAs, smart phones and wireless sensors brings the best out of mobile computing particularly mobile ad-hoc and sensor networks. Nowadays, most of researchers working on Wireless Sensor Networks (WSNs) focus on Mobile Ad-hoc and Sensor Networks (MASNETs) due to their wide range of potential applications ranging from underwater monitoring to search and rescue mobile robotics applications. In this research work, through extensive simulation, we have evaluated the capability of Ad-hoc On Demand Distance Vector (AODV) routing protocol on how far it can react to different mobility duration of mobile nodes in MASNETs. The performance of AODV is investigated in terms of the average percentage of packet loss and energy consumption. The initial performance study demonstrates that the performance of AODV is signicantly decreased in mobile environment due to the frequent topology change in MASNETs. Therefore, in order to enhance the performance of AODV in MASNETs, the new routing algorithm based on the estimated distance is proposed to replace the hop count for the selection of next node during the packet transmission. The estimated distance is computed based on the Received Signal Strength Indicator (RSSI) values that are collected during the communication between the sensor nodes. The performance of the proposed solution is also further evaluated and compared with the existing AODV routing protocol in term of their energy consumption and percentage of packet loss. Our study demonstrates that the proposed solution outperform the existing AODV in MASNETs.